2015
DOI: 10.1055/s-0035-1556749
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Withdrawal Identification and Management

Abstract: Sedation administered by continuous intravenous infusion is commonly used in the pediatric intensive care unit to facilitate and maintain safe care of children during critical illness. Prolonged use of sedatives, including opioids, benzodiazepines, and potentially other adjunctive agents, is known to cause withdrawal symptoms when they are stopped abruptly or weaned quickly. In this review, the common signs and symptoms of opioid, benzodiazepine, and dexmedetomidine withdrawal will be discussed. Current tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…While hypoxemia is a potential cause for the neurologic signs in these cases, it is less likely based on the lack of other neurologic deficits to support a diagnosis of hypoxic brain injury. Additionally, while these dogs received multiple sedatives, withdrawal of these drugs, including opioids and alpha antagonists, is associated with signs such as tremors and agitation but has not been associated with seizures, making benzodiazepine withdrawal the most likely scenario in all 3 cases 21 . Due to the temporary lateralizing neurologic deficits in case 1, it is possible that the cause of this dog's seizures was multifactorial including the combination of a forebrain lesion and acute benzodiazepine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…While hypoxemia is a potential cause for the neurologic signs in these cases, it is less likely based on the lack of other neurologic deficits to support a diagnosis of hypoxic brain injury. Additionally, while these dogs received multiple sedatives, withdrawal of these drugs, including opioids and alpha antagonists, is associated with signs such as tremors and agitation but has not been associated with seizures, making benzodiazepine withdrawal the most likely scenario in all 3 cases 21 . Due to the temporary lateralizing neurologic deficits in case 1, it is possible that the cause of this dog's seizures was multifactorial including the combination of a forebrain lesion and acute benzodiazepine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by a Regional Board of Ethics in Sweden and permission to contact the participants was given by the head of the department. The study was conducted in accordance with the Declaration of Helsinki ( World Medical Association, 2013 ) and the four basic principles of research ethical principles in medical human research. All informants were guaranteed confidentiality and written informed consent was obtained from all study participants.…”
Section: Methodsmentioning
confidence: 99%
“…When a child is admitted to the Pediatric Intensive Care Unit (PICU), the care usually entails a mix of drug infusions. Sedative and analgesic drugs are administered as they enable treatment, and relieve discomfort and pain associated with the treatment of children ( Playfor & Vyas, 2000 ; Tonner et al, 2003 ; Whelan et al, 2015 ). The administration of potent opiates and sedative drugs are needed to facilitate respiratory care, prevent accidental self-extubation, and reduce stress and anxiety ( Playfor & Vyas, 2000 ; Tobias & Rasmussen, 1994 ; Tonner et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Nonetheless, assessment, prevention, and management of IWS continue to be challenging. 9 Best et al identified risk factors associated with IWS and found that duration of therapy and cumulative doses of opioids and benzodiazepines are the most predictive factor of IWS. 10 They also highlighted the need to further explore process, and system variables, such as sedation/IWS assessment, and protocol adherence.…”
Section: Introductionmentioning
confidence: 99%